Cycles of Malnutrition: Intergenerational Health Transmission in India - Santosh Kumar Gautam; Timothy J. Halliday; Bhash Mazumder (Institute of Labor Economics (IZA), 2025)
We provide the first estimates of broad-based health transmission between parents and their young children in India. The correlations between maternal health and child health outcomes—such as anemia, stunting, and body mass index—are approximately 0.20. When aggregating these health measures into a general index of latent health, we estimate a correlation of 0.22, comparable to intergenerational persistence estimates in other countries. Absolute health mobility is lower for poorer households and for scheduled castes and scheduled tribes. We document significant geographic heterogeneity in health transmission, lower mobility in northern and central India, and higher mobility in the southern regions. Consistent with this pattern, states with higher poverty rates and higher anemia prevalence tend to exhibit lower upward mobility.
Keywords: I14; I15; O12; 330; intergenerational mobility; anemia; stunting; latent health; nutrition; India